Microbial Grazers May Aid in Controlling Infections Caused by the Aquatic Zoosporic Fungus Batrachochytrium dendrobatidis - Farthing, Hazel N.; Jiang, Jiamei; Henwood, Alexandra J.; Fenton, Andy; Garner, Trent W. J.; Daversa, David R.; Fisher, Matthew C.; Montagnes, David J. S. (Frontiers in Microbiology, 2021)
Free-living eukaryotic microbes may reduce animal diseases. We evaluated the dynamics by which micrograzers (primarily protozoa) apply top-down control on the chytrid Batrachochytrium dendrobatidis (Bd) a devastating, panzootic pathogen of amphibians. Although micrograzers consumed zoospores (~3 µm), the dispersal stage of chytrids, not all species grew monoxenically on zoospores. However, the ubiquitous ciliate Tetrahymena pyriformis, which likely co-occurs with Bd, grew at near its maximum rate (r = 1.7 d-1). A functional response (ingestion vs. prey abundance) for T. pyriformis, measured using spore-surrogates (microspheres) revealed maximum ingestion (Imax) of 1.63 x 103 zoospores d-1, with a half saturation constant (k) of 5.75 x 103 zoospores ml-1. Using these growth and grazing data we developed and assessed a population model that incorporated chytrid-host and micrograzer dynamics. Simulations using our data and realistic parameters obtained from the literature suggested that micrograzers could control Bd and potentially prevent chytridiomycosis (defined as 104 sporangia host-1). However, simulated inferior micrograzers (0.7 x Imax and 1.5 x k) did not prevent chytridiomycosis, although they ultimately reduced pathogen abundance to below levels resulting in disease. These findings indicate how micrograzer responses can be applied when modelling disease dynamics for Bd and other zoosporic fungi.